Temporal changes of taxonomic and functional diversity in dung beetles inhabiting forest fragments and pastures in Los Tuxtlas Biosphere Reserve, Mexico - Pedro Giovâni da Silva; Renato P. Salomão; Daniel González-Tokman; Frederico S. Neves; Mario E. Favila (Revista Mexicana de Biodiversidad)
We evaluated short- (among months within-years) and long-term (between 1999-2000 and 2016-2017) temporal patterns of taxonomic and functional β- diversity (and its components of substitution and gain/loss) of dung beetle assemblages in forest  fragments and pastures in the Los Tuxtlas Biosphere Reserve (LTBR). Habitat type affected the taxonomic dissimilarity and the richness difference component, with average values being respectively 1.42 and 1.56 times higher in pastures than in forest fragments. Only habitat type was important for functional  richness, being 1.93 and 1.69 higher in forest fragments than pastures in 1999-2000 and 2016-2017, respectively. Pastures were taxonomically and functionally poorer but were also more temporally dynamic than forest fragments both within-year and between-years. Habitat type is a determining factor for temporal dynamics, with forest fragments presenting more stable dung beetle assemblages than cattle pastures.